Boganmeldelser - Flaatten, Sverre; Nordlöf, Kerstin; Brydensholt, Hans Henrik; Kyvsgaard, Britta; Garde, Peter; Ryberg, Jesper; Havelund, Jonas (Nordisk Tidsskrift for Kriminalvidenskab, 2009)
Book reviews